Company analysis: ASUS / Nur Sabrina Hussaini - Hussaini, Nur Sabrina (2022)
I was able to determine the strengths and limitations of the company's footholds by the use of SWOT analysis. Once I've looked over the strengths and weaknesses, I'll be able to draw on the strengths and focus on the weaknesses in order to turn them into leverage in the future. Based on the findings, I can deduce that the defects in the product are related to the problems and issues that occur. Even if the product we want to create has shortcomings and disadvantages, it is normal for modern products to evolve with new technology. The distinction between opportunity and danger is blurry since some opportunities may pose a threat, but every threat presents an opportunity to learn something new. If I am to succeed in business, I must always be careful and take calculated risks. Using those words as a metaphor, technological advance mentor enhancement is often a risky step, but it can be mitigated with a detailed demand and product or service review.